Efforts to Improve Learning Outcomes Using Video Media for Grade 6 Students of Wadasmalang 3 Public Elementary Schools, Karangsambung District Kebumen Academic Year 2020/2021 - Triyono Triyono (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in learning theme 5 in grade VI elementary schools using video learning media. The research conducted was a Classroom Action Research (CAR) consisting of three cycles. The stages of each cycle were planning, implementing, observing and reflecting. Each meeting is carried out an assessment of knowledge, skills and attitudes to determine the development of students. In cycle I, students who completed after carrying out the knowledge assessment were 70%. In cycle II students who completed after carrying out the knowledge assessment were 87%. In cycle III students who completed after carrying out the knowledge assessment were 93%. These results indicate that the use of video media can improve student learning outcomes, especially the theme of Class VI at SDN 3 Wadasmalang.